Features of the course of corneal and choroidal inflammation in children infected with SARS-CoV-2 (Ukrainian Journal of Ophthalmology, 2025)
Background: The consequences of respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemics are still unfolding.Purpose: To examine the course of corneal and choroid inflammation in children infected with COVID-19 who were treated at the Department of Pediatric Eye Pathology, SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine”, in 2021-2023.Material and Methods: The study sample included 62 children (94 eyes) with corneal and choroidal inflammation who were treated at the Department of Pediatric Eye Pathology, SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine”, in 2021-2023. SARS-CoV-2 infection was confirmed by laboratory testing in all children. The age of children ranged from 6 months to 17 years (mean age, 10.67 ± 2.95 years). Enzyme-linked immunosorbent assay (ELISA) was used to detect SARS-CoV-2- immunoglobulin (Ig)M antibodies in children suspected for past COVID-19 infection.Results: The detection of immunoglobulin IgM antibodies indicated a recent past SARS-CoV-2 infection, whereas positive COVID-IgG indicated a prior past infection. Uveitis was the most common ocular finding (48/62 children (77.4%), 78 eyes); 77% of uveitis cases were bilateral. Acute uveitis, acute exacerbation of chronic uveitis and sequelae of chronic uveitis were observed in 33.3%, 53.9%, and 12.8%, respectively, of study eyes. Panuveitis with severe complications (seclusio and occlusio papillae, uveal cataract, secondary glaucoma, retinal detachment, subretinal neovascular membranes, vitreous hemorrhage, vitreous fibrosis and phthisis bulbi) was diagnosed in 57.7% of study eyes, mostly in eyes with bilateral uveitis. Post-COVID-19 keratitis was found in 14 children (16 eyes; 12.4%) and was unilateral in 85.7% and acute in 62.5% of cases.Conclusion: Past SARS-CoV-2 infection may cause an acute ocular inflammatory disease or recurrent chronic inflammatory process in children. Uveitis with lesions in all uveal tract compartments and severe complications was the most common finding. Family doctors should be encouraged to refer all children with a past COVID-19 infection to an ophthalmologist. Pediatric ophthalmologists should be aware of possible post-COVID-19 ocular complications.
Keywords: COVID-19; ocular manifestations; uveitis; keratitis; children; ocular inflammatory disease